2018
DOI: 10.1177/0284185118768098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bismuth breast shielding on iodine quantification in dual-energy computed tomography: an experimental phantom study

Abstract: Although using the bismuth breast shield may decrease radiation exposure to the breast on DECT, it may also significantly affect iodine quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, the fact of beam hardening leads to an unpredictable change of Hounsfield units, thereby challenging for any quantitative image analysis, e.g. for coronary CT angiography or iodine quantification [43,66,67]. In addition, if authors conclude that despite the shielding causing higher noise levels a sufficient diagnostic image quality was achieved, then, one has at least to reconsider whether the original protocol would allow for dose savings based on optimized scanning parameters instead of contact in-plane-shielding.…”
Section: In-plane Shieldingmentioning
confidence: 99%
“…However, the fact of beam hardening leads to an unpredictable change of Hounsfield units, thereby challenging for any quantitative image analysis, e.g. for coronary CT angiography or iodine quantification [43,66,67]. In addition, if authors conclude that despite the shielding causing higher noise levels a sufficient diagnostic image quality was achieved, then, one has at least to reconsider whether the original protocol would allow for dose savings based on optimized scanning parameters instead of contact in-plane-shielding.…”
Section: In-plane Shieldingmentioning
confidence: 99%
“…Many studies showed that CT scans increase the incidence of cancer risk (2,3). The dose of the superficial organs in CT scan examination is high and the breast is one of the organs that is directly irradiated through thoracic CT scans and it is also a sensitive organ to radiation (4). Breast cancer is one of the most important reasons causing death in women; therefore, the strategy of radiation protection must be used in order to reduce radiation dose to these organs (5).…”
Section: Introductionmentioning
confidence: 99%